IMPLEMENTASI KEBIJAKAN PAJAK REKLAME PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KABUPATEN MINAHASA - TOLOLIU, ANDRE WILDY; OGOTAN, MARTHA; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
The research objective was determine the implementation of advertisement tax policy in the tax and retribution management body in the Minahasa district. This study uses qualitative approach of informants in this study as many as 5 people, namely the head of the agency, the head of the data collection field, an executor, and an advertisement taxpayer. Data collection uses interview and observation guidelines; while the analytical technique used is an interactive analysis model from Miles and Hubernann. Based on the results of the data analysis, it was concluded that the implementation of the advertisement tax policy in the tax and retribution management body in the Minahasa regency viewed from the dimensions of the idealized policy, the target groups dimensions, the implementing organization dimension, and the dimensions of environmental factors, were not optimal. Based on the conclusions the results of the study are recommended: (1) the dimensions of the â€œidealized policyâ€ need to be improved by building more effective communication with the subjects of advertisement tax, as well as increasing coordination with relevant parties; (2) The dimensions of â€œtarget groupsâ€ needs to be increased by taking nore effective actions to increase the awareness of the subject of tax compliance with their tax obligations; (3) The dimensions of â€œImplementing organizationâ€ needs to be improved by optimizing the implementation of the duties and fuctions of the unit/unit of the organization responsible for managing advertisement tax; (4) the dimensions of â€œenvironmental factorsâ€ needs to be improved by seeking to create more conducive social and cultural conditions. Keywords : Policy Implementation, Advertisement Tax